Practicing Collective Biography. Issue 4 (April 2016) - Hawkins, Roberta; Falconer Al‐Hindi, Karen; Moss, Pamela; Kern, Leslie
Abstract: Collective biography uses researchers' written memories about a set of experiences as texts for collective analysis. As a feminist approach to research, collective biography draws centrally on the idea that significant memories are critical in the constitution of the self, and maintains that in analyzing memories collectively, researchers can begin to tap into wider social processes and structures. Though rarely used in geography, collective biography could be useful in data collection and analysis for geographers. In this paper, we provide a brief history and description of collective biography. We situate collective biography in relation to life writing methods. We then identify a set of attributes that mark collective biography as a distinct research approach. In closing, we reflect on our experiences working with collective biography.